Bibliometric analysis of RNA-binding proteins in osteosarcoma: unraveling research trends and hotspots - Gu, Zhiqian; Zhang, Songou; Hu, Xudong; Xu, Nanjian; Wang, Yang; Ruan, Jian; Qian, Yufeng; Ma, Weihu; Chen, Hong (Frontiers in Immunology, 2025)
BackgroundRNA-binding proteins (RBPs), a class of molecules that play a crucial role in regulating gene expression, have attracted considerable attention in cancer biology research. RBPs influence osteosarcoma progression by modulating RNA metabolism and participating in cellular proliferation, differentiation, apoptosis, and interactions within the tumor microenvironment. Understanding the current status and future trends of RBPs is crucial for the advancement of osteosarcoma research.MethodsRelevant literature was sourced from the Web of Science, PubMed, and Scopus databases covering the period from January 1, 1994, to December 31, 2024. Using professional analytical tools such as R bibliometrix, VOSviewer, CiteSpace, and SCImago, we conducted a multidimensional visual analysis of publication trends, contributions from countries and institutions, influential authors, significant publications, and keyword distribution.ResultsResearch on RBPs in osteosarcoma began in 1994, with a notable increase in published studies since 2016. The leading countries for research output were China and the United States, primarily from three major U.S. institutions: the University of Illinois, Harvard University, and UT MD Anderson Cancer Center. Significant contributors to this field included Kannanganattu V. Prasanth, Jean-Yves Masson, Yang Wang. The most cited article was a review titled The potential role of RNA N6-methyladenosine in Cancer progression by Professor Shaoqing Ju from China (2020). Prominent journals within this domain included Cancer Research (USA), Oncogene (England), Cancer Cell International (England), and the Journal of Bone and Mineral Research (USA).ConclusionThis study highlights the critical role of RBPs in osteosarcoma. We conducted a systematic literature review using bibliometric methods to outline the research landscape, identify hotspots and emerging trends, and provide valuable references for future studies. Future research should focus on enhancing international collaboration, exploring molecular mechanisms, and connecting these insights to clinical applications—especially in targeted drug development—to improve treatment outcomes for osteosarcoma patients.